Analisis Dispersi Udara Ambien dengan Parameter CO dan Kebisingan di Terminal Alam Barajo - Ghina Rinanda Putri; Peppy Herawati; Asih Suzana (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Alam Barajo Terminal constitutes a public service unit administered by the Class II Jambi Land Transportation Management Center. The substantial vehicular intensity within the precinct has progressively amplified ambient air pollutant levels, most notably carbon monoxide (CO) and acoustic disturbance. This investigation was undertaken to quantify CO concentrations and noise levels in the ambient atmosphere, whilst simultaneously delineating the dispersal pattern of CO concentration at Alam Barajo Terminal employing the AERMOD modelling approach, within a quantitative descriptive research framework. Empirical findings disclosed that CO concentration recorded on Monday between 07.00–08.00 at Point I reached 10,115 µg/Nm³, surpassing the permissible threshold of 10,000 µg/Nm³ as stipulated under Government Regulation Number 22 of 2021. AERMOD dispersion modelling further revealed a maximum CO emission concentration of 48,377 µg/Nm³ in the ambient atmosphere, whilst the minimum concentration registered 10,900 µg/Nm³. Regarding acoustic parameters, the peak noise level was documented on Friday at Point I, reaching 75.5 dBA, whereas the lowest reading was recorded on Monday at Point II at 53.6 dBA, both assessed against the 60 dB(A) quality benchmark prescribed under Minister of Health Regulation No. 2 of 2024.